Ant-pro reverse-turn motif. structural features and conformational characteristics - Thorat, Vijaykumar H.; Ingole, Tukaram S.; Vijayadas, Kuruppanthara N.; Nair, Roshna V.; Kale, Sangram S.; Ramesh, Veera V. E.; Davis, Hilda C.; Prabhakaran, Panchami; Gonnade, Rajesh G.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; et al. (European Journal of Organic Chemistry, 2013)
This article details the characteristic conformational features of the Ant-Pro reverse turn ? a folded pseudo -turn motif that displays a closed nine-membered-ring hydrogen-bonded network involving just two amino acid residues, namely anthranilic acid (Ant; a constrained -amino acid), and proline (Pro; a constrained -amino acid). The results from the extensive investigation of ten crystal structures and their NMR conformations in the solution state provide a clear idea about the conformational characteristics of the Ant-Pro reverse turn. The Ant and Pro residues, which form the turn segment, maintain a perfect antiperiplanar orientation throughout, leaving little possibility for the formation of the otherwise possible six-membered hydrogen-bonding that requires a coplanar disposition of the two amino acid residues, as clearly evident from investigation of several crystal structures. The closed hydrogen-bonded network observed in the Ant-Pro reverse turn motif, formed in the forward direction of the sequence (12 amino acid interactions) involving only two amino acid residues, is in stark contrast to the native -turns that involve four residues to form hydrogen-bonded network featuring backward 14 amino acid interactions. The readily available two-residue Ant-Pro motif raises the possibility of a practical utility, particularly in the application of rigidifying flexible peptide backbones by inserting the robust Ant-Pro reverse turn motifs into their backbone.
Keywords: Peptides; Peptidomimetics; Protein folding; Protein structures

Synthetic turn mimetics and hairpin nucleators: quo vadimus? - Nair, Roshna V.; Baravkar, Sachin B.; Ingole, Tukaram S.; Sanjayan, Gangadhar J. (Chemical Communications, 2014)
Structural mimicry of peptides has witnessed perceptible progress in the last three decades. Reverse turn and beta-hairpin units are the smallest secondary structural motifs that are some of the most scrutinized functional cores of peptides and proteins. The practice of mimicking, without altering the function of the bioactive core, ranges from conformational locking of the basic skeleton to total replacement of structural architecture using synthetic analogues. Development of heterogeneous backbones - using unnatural residues in place of natural ones - has broadened further opportunities for efficient structural rigidification. This feature article endeavours to trail the path of progress achieved hitherto and envisage the possibilities that lie ahead in the development of synthetic turn mimetics and hairpin nucleators.

3-Aminothiophenecarboxylic acid (3-Atc)-induced folding in peptides - Ingole, Tukaram S.; Kotmale, Amol S.; Gawade, Rupesh L.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (New Journal of Chemistry, 2016)
This paper describes the consequences of incorporating a constrained heterocyclic aromatic b-amino acid 3-aminothiophenecarboxylic acid (3-Atc) into peptides containing beta-turn forming elements such as Pro-Gly motif and the effect on the secondary structural architecture of the entire peptide backbone. Conformational investigations of oligomers comprising an alpha,beta,alpha peptide sequence were carried out by single-crystal X-ray diffraction, solution-state NMR, nOe-restrained MD simulation and circular dichroism studies. The results suggested that these peptide sequences assume helical architecture. The helical folding in the oligomers was found to be devoid of inter-residual H-bonding, instead found to be stabilized by a co-operative effect of 6-membered H-bonding within the 3-Atc unit and conformational restrictions of individual amino acids in the peptide backbone.

Disruption of native beta-turns: consequence of folding competition between native and orthanilic acid proline-based pseudo beta-turn - Ingole, Tukaram S.; Vijayadas, Kuruppanthara N.; Chaitanya, K. N.; Kotmale, Amol S.; Gawade, Rupesh L.; Gonnade, Rajesh G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (European Journal of Organic Chemistry, 2016)
Five tetrapeptides comprising beta-turn-forming elements and a pseudo beta-turn (C9 H-bonding) based on an SAntPro (orthanilic acid - proline) motif were designed and synthesized. Their extensive conformational investigation by single-crystal X-ray crystallography, solution-state 2D NMR spectroscopic, and nOe-restrained MD simulation studies revealed the formation of C14 or C9 folding and disruption of the native beta-turn (C10 H-bonding) architecture. The striking difference between the psi(psi(2)) angle of ``i + 2'' residues of native beta-turn and designed peptides suggest that formation of the native beta-turn is not favored. The results suggest that other turn-forming motifs can dramatically modulate the stability of the native beta-turn structure.
Keywords: Conformation analysis; hydrogen bonds; Peptidomimetics; structure elucidation

Self-assembled vesicles of urea-tethered foldamers as hydrophobic drug carriers - Ingole, Tukaram S.; Kale, Sangram S.; Sukumaran, Santhosh Babu; Sanjayan, Gangadhar J. (Chemical Communications, 2016)
Molecular self-assembly of nonamphiphilic alpha,beta-hybrid foldamers based on urea-tethered anthranilic acid-proline (Ant-Pro) foldamers is reported. These self-assembled hollow vesicular architectures can take up and release the anticancer hydrophobic drug curcumin.